2016
DOI: 10.4269/ajtmh.15-0730
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Predictors of Care-Seeking Behaviors Among Caregivers of Febrile Children—Uganda, 2009

Abstract: Abstract. Fever is a major cause of morbidity and mortality among children under 5 years of age in resource-limited countries. Although prevention and treatment of febrile illnesses have improved, the costs-both financial and nonfinancialremain barriers to care. Using data from the 2009 Uganda Malaria Indicator Survey, we describe the costs associated with the care of a febrile child and assess predictors of care-seeking behavior. Over 80% of caregivers sought care for their febrile child, however less than ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The high direct costs for management of malaria episodes resulting in hospitalization in Malawi are similar to those observed in Mozambique, Ghana, and Uganda for inpatient management of malaria episodes [ 9 , 10 , 33 ], and less than reported for severe malaria patients in Sudan where direct household costs averaged $17.20 ($22.30 in constant 2012 US dollars) for the management of severe malaria episodes [ 11 ]. This may be in part due to differences in study design; the Sudan study only reviewed costs for patients hospitalized and treated for severe or complicated malaria, whereas this study included all hospitalized patients who received anti-malarial treatment, and did not discriminate between patients with different malaria diagnoses or severity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The high direct costs for management of malaria episodes resulting in hospitalization in Malawi are similar to those observed in Mozambique, Ghana, and Uganda for inpatient management of malaria episodes [ 9 , 10 , 33 ], and less than reported for severe malaria patients in Sudan where direct household costs averaged $17.20 ($22.30 in constant 2012 US dollars) for the management of severe malaria episodes [ 11 ]. This may be in part due to differences in study design; the Sudan study only reviewed costs for patients hospitalized and treated for severe or complicated malaria, whereas this study included all hospitalized patients who received anti-malarial treatment, and did not discriminate between patients with different malaria diagnoses or severity.…”
Section: Discussionmentioning
confidence: 79%
“…Travel costs accounted for an average of 48% of direct household expenditures, and households that lived less than 5 km away from the health facility incurred a 40% lower cost per episode compared to those who lived 5 km or more away. Previous studies have shown that increased costs limit treatment seeking behavior in harder to reach households (those more than 5 km away from health facilities) [ 19 , 33 ], and may account for substantial delays in accessing care [ 35 ]. Distance to a health facility and associated travel costs may, therefore, constitute a major financial burden for low income families as well as a significant barrier to prompt care-seeking, which could in turn contribute to negative health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Though more than half the guardians reported duration of symptoms before seeking treatment as 24 h, up to 40.1% presented after 24 h, slightly lower than other study findings [ 36 , 37 ]; worryingly, 18.3% presented after 48 h of symptoms. Although the sample was not powered to evaluate factors associated with delays in seeking care, some of the findings in the survey such as low level of education, distance to facility, and rural communities have been reported as significant contributors to care-seeking behaviour [ 38 41 ]. Delay in treatment increases the risks of morbidity and mortality, and propagates malaria transmission as the patient remains infectious for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The non-RA children who went to a health centre paid on average $6.56 ($8.09 if they had CNS symptoms and $5.72 if they had repeated vomiting/lethargy). Menon et al [ 24 ] found similar results ($6.84) in Uganda and other studies reported similar out-of-pocket costs (Ghana: $6.40 for severe cases; Malawi: $5.30 for children under 5) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 62%
“…In CRFs, information was sought about the characteristics of the child and households (sex, age, education, occupation, household food scarcity, the number of working people over 10 years old), the date and clock time from onset of each symptom, the date and clock time of visit (for each provider visited) and the out-of-pocket costs associated with each visit. Guardians provided detail about the costs incurred at each healthcare provider for registration, consultation, diagnosis, drugs, bed, food/drinks and transport [ 14 , 24 26 ]. All data were reported by the guardians from memory and the same interviewers were used for all household interviews to minimize interviewers’ bias.…”
Section: Methodsmentioning
confidence: 99%